Inside bluetooth low energy - Gupta, Naresh C. (Naresh Chand) (Artech House mobile communications series, 2013)
Bluetooth Low Energy (LE) is one of the latest enhancements to Bluetooth technology and, as the name suggests, it is aimed at ultra low power devices, such as heart rate monitors, thermometers, and sensors. Due to very low power consumption, devices compliant with this standard can operate for several years on coin cell batteries without the need for recharging. This cutting-edge book helps you understand the whats, whys, and hows of Bluetooth LE. It includes a broad view of the technology, identifies the various building blocks, and explains how they come together. You also find discussions on Bluetooth basics, providing the background information needed to master Bluetooth LE"--Back cover